DECENTRALIZED WASTEWATER TREATMENT SYSTEM (DEWATS) AS A MODERN APPROACH FOR WASTEWATER MANAGEMENT IN EGYPT, REVIEW - Attia, Walid A.; Mohamed, Ahmed S. Mohamed; El-Taweel, Ahmed A. (Acta Scientiae et Intellectus, 2024)
The main aim of this study was to present a review about Decentralized Wastewater Treatment Systems (DEWATS) as a tool for wastewater treatment that could be applied in Egypt. In Egypt, from the south of Giza to Aswan (Upper Egypt), people live very near to the shores of the river Nile. The cities and big villages lie on River Nile and bounded with the river banks at one side and with mountains and desert from the other side. The great challenge is to save lands for domestic life and cultivation. The limited area and the finite available land between the Nile and the Mountain present difficulty for expansion and industrial and social development. Decentralized wastewater treatment systems (DEWATS) includes only such systems which are considered suitable for decentralized applications and dissemination in the case that qualified maintenance and operation cannot be expected.